Customer Satisfaction Pengaruhnya Terhadap Brand Preference dan Repurchase Intention Private Brand - Ardhanari, Margaretha (Jurnal Riset Ekonomi dan Bisnis, 2008)
The objectives of this study are to know the influence of customer satisfaction on brand preference for private brand product, to know the influence of brand preference on repurchase intention for private brand product, and to examine the influence of customer satisfaction on repurchase intention of private brand product. The result of this study for customer satisfaction has positive impact on brand preference with private brand in Matahari Dept. Store Surabaya. This shows us if it gives better satisfaction also gives good impact on the brand preference. Brand preference gives positive impact on repurchase intention to private brand product in Matahari Dept. Store Surabaya. It also shows us that the better brand preference for the consumers, make the better repurchase intention. Customer satisfaction gives positive impact on repurchase intention in private brand Matahari Dept. Store Surabaya. It also shows us that the better customer satisfaction, make the repurchase intention get better.Keywords: Customer Satisfaction, Brand Preference, Repurchase Intention, Private Brand